A series of Zn(ii) terpyridine complexes with enhanced two-photon-excited fluorescence for in vitro and in vivo bioimaging1. Issue 36 (28th September 2015) - Zhang, Qiong; Tian, Xiaohe; Hu, Zhangjun; Brommesson, Caroline; Wu, Jieying; Zhou, Hongping; Li, Shengli; Yang, Jiaxiang; Sun, Zhaoqi; Tian, Yupeng; Uvdal, Kajsa
<x xml:space="preserve">Abstract</x> TPA cross sections are enhanced for the complexes containing D–A type ligand L1. 1 exhibits specificity in two-photon fluorescence imaging.